Microwave-Assisted Pyrolysis of Rice Husk Waste Using Silicon Carbide: Effects of Particle Size and Holding Time - Zaka, Ahmad Murtadlo; Saptoadi, Harwin; Putra, Robertus Dhimas Dhewangga (Chemical Engineering Journal Storage (CEJS), 2025)
Microwave pyrolysis converts rice husk waste into biochar, bio-oil, and gas products. This research utilized a microwave oven and a conventional oven to process rice husk into pyrolysis products, with silicon carbide (SiC) serving as an absorber in the primary microwave reactor and a natural zeolite catalyst in the secondary oven reactor. The particle size variations of rice husk waste were 2-1 mm, 1-0.5 mm, and 0.5-0.25 mm, with holding times of 5, 10, 15, and 20 minutes. The smallest particle size (0.25-0.5 mm) exhibited the fastest and most consistent heating rate, reaching 400 ËšC in 900 seconds and 450 ËšC in 1268 seconds. The highest biochar yield was obtained at a 5-minute holding time, whereas the highest bio-oil yield was achieved at 20 minutes. The highest gas yields for 1-2 mm (17.80%) and 0.5-1 mm (17.90%) were achieved at 5 minutes of holding time, whereas 0.25-0.5 mm particles yielded the highest gas (21.60%) at 20 minutes. The highest total energy of 1.153 MJ was obtained at size 1-2 with a holding time of 10 minutes and size 0.5-1 mm with a holding time of 5 minutes, while 0.25-0.5 mm particles reached 1.122 MJ at 10 minutes. The highest energy efficiency was achieved at a holding time of 5 minutes, recorded at 21.44% for particles sized 0.25-0.5 mm. This value is higher compared to particles sized 0.5-1 mm (21.21%) and 1-2 mm (19.84%). These results contribute to the optimization of rice husk waste management and the sustainable utilization of biomass